2014
DOI: 10.1159/000356649
|View full text |Cite
|
Sign up to set email alerts
|

Heme Oxygenase-1 Mediates Oxidative Stress and Apoptosis in Coxsackievirus B3-Induced Myocarditis

Abstract: Background: Heme oxygenase-1 (HO-1), which is suggested to play a role in defending the organism against oxidative stress-mediated injuries, can be induced by diverse factors including viruses and iron. As coxsackievirus B3 (CVB3)-infected SWR/J mice susceptible for chronic myocarditis were found to have a significant iron incorporation and HO-1 upregulation in the myocardium, we aimed to investigate the molecular interplay between HO-1 expression and iron homeostasis in the outcome of viral myocarditis. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 33 publications
(43 reference statements)
2
29
1
Order By: Relevance
“…by inhibition of iNOS in macrophages of mice [43]. The activity of iNOS increased with all tested concentrations of equol used here with chicken macrophages, contrasting with equol inhibiting nitric oxide content and iNOS gene expression in murine macrophages [42].…”
Section: Discussionmentioning
confidence: 72%
“…by inhibition of iNOS in macrophages of mice [43]. The activity of iNOS increased with all tested concentrations of equol used here with chicken macrophages, contrasting with equol inhibiting nitric oxide content and iNOS gene expression in murine macrophages [42].…”
Section: Discussionmentioning
confidence: 72%
“…Additionally, inhibition of cell apoptosis is one of the important mechanisms that lead to the exacerbation of inflammation. Published studies show that HO-1 is capable of anti-apoptosis 47 and pro-apoptosis 1,48,49 functions depending on the cell type and disease model. In the present study, we found that up-regulation of HO-1 can promote basophil apoptosis, which contributed to the remission of allergic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…HO is the rate-limiting enzyme for degradation of heme [32]. Large amount of evidence has shown that HO plays an important in cellular protection against inflammation and oxidative stress [33][34][35][36][37]. HO-1 is an inducible isoform of HO, which plays an important role in skin injury and wound healing.…”
Section: Discussionmentioning
confidence: 99%